2018
DOI: 10.1021/acsomega.8b00159
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Versatile Method for the Formation of Acetals/Ketals Using Trace Conventional Acids

Abstract: An important and surprising finding that the acetalization and ketalization of aldehydes and ketones with alcohols, respectively, proceed smoothly in the presence of 0.1 mol % acid, without removing water, has been presented. This process has many merits, such as commercial available catalysts with low cost and low loadings (as low as 0.03 mol %), quite a broad substrate scope (including various aldehydes, ketones, acid-sensitive substrates, and diols), a wide range of reaction temperature (−60 to 50 °C), high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 67 publications
0
54
0
1
Order By: Relevance
“…Thus, as expected, the corresponding acetal products 2 were obtained in excellent yields up to the fifth cycle at room temperature. It is noteworthy that the same reaction under mineral acid catalysis was failed to resue . These results suggest that the present acetalization does not follow the classical (mineral) acid catalysed pathway.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…Thus, as expected, the corresponding acetal products 2 were obtained in excellent yields up to the fifth cycle at room temperature. It is noteworthy that the same reaction under mineral acid catalysis was failed to resue . These results suggest that the present acetalization does not follow the classical (mineral) acid catalysed pathway.…”
Section: Methodsmentioning
confidence: 91%
“…Notably, when we reduce the catalyst loading from 1 mol % to 0.01 mol % the reaction preceded smoothly and afforded the desired product 2 a in excellent yield (Table , entries 11–12). A control experiment with 2‐methyl 2‐butene (radical and chloride quencher) showed that this reaction does not follow the classical mineral acid catalytic pathway (Table , entry 15). Indeed, increasing the temperature does not have any influence on product formation (Table , entry 14).…”
Section: Methodsmentioning
confidence: 98%
“…The ketalization of carbonyl compounds with diols is a common transformation (Figure 12), which is typically implemented to ensure chemoselective transformation upon protection of aldehydes or ketones within the frame of complex organic synthesis, [197] though it also concerns the production of fuel additives and the manufacturing of building blocks toward high added‐value. Ketals have also a promising future in the polymer industry as biodegradable smart polymers [198] .…”
Section: Staple Reactions Toward the Upgrading Of Bio‐based Vicinal P...mentioning
confidence: 99%
“…Además, se han llevado a cabo estudios experimentales (Trifoi et al, 2016), (Ferreira et al, 2019); trabajos teóricos (Azofra et al, 2012) sobre síntesis de hemiacetales y estudios donde dicha reacción puede ser catalizada por medio de una base (Funderburk et al, 1978), (Grabowski et al, 2018) de un ácido de Brönsted (Dong et al, 2018), (Yang et al, 2005), de un ácido de…”
Section: Introductionunclassified